"A heart attack away from boarding up Main Street": How neoliberalization of farming shapes adaptive capacity to climate change in rural and small-town Saskatchewan, Canada. (January 2023) - Campbell-Gale, Holly K.; Fletcher, Amber J.; Reed, Maureen G.
Abstract: Research shows that climate change vulnerability is constituted not only by exposure to adverse climate conditions, but also by social and economic factors. Even for areas that currently have limited exposure, social and economic structures have a role in shaping adaptive capacity. Focusing on two rural municipalities in the province of Saskatchewan, Canada, this study explores how social and economic trends, identified as the neoliberalization of farming, have affected adaptive capacity to climate change in one of Canada's primary agricultural regions. Using interview data and participant observation, this study explores farm consolidation, patterns of consequent depopulation and weakened infrastructure, and how these realities operate in conjunction with disaster exposure to create conditions of reduced adaptive capacity, ultimately increasing vulnerability for small prairie communities. This research makes a contribution toward linking climate change adaptive capacity to broader patterns of neoliberalization in agriculture using empirical qualitative data. Highlights: Economic drivers shape climate change vulnerability in rural Saskatchewan. Consolidated farming in Canadian Prairies exacerbates climate change sensitivity. Depopulation and weakened social infrastructure amplify climate sensitivity. Neoliberalization weakens adaptive capacity in the Canadian Prairies. Economic shifts in farming combine with exposure to increase vulnerability.